2022
DOI: 10.31219/osf.io/j54bx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Harezmi Education Model on the Computational Thinking Skills of Secondary School Students

Abstract: This study aims to investigate the effect of using the Harezmi education model, which has been widely used in Turkey in recent years, in social studies teaching regarding computational thinking skills. Interviews were held with students and teachers seven months after the applications to determine the conceptual knowledge levels of students for computational thinking skills. Teachers' opinions regarding students' feedback and the changes they observed in the students involved in the application process during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although there are no studies on science lesson in the literature, studies indicate that they improve student achievement in social studies courses (Tokmak, 2022). Tokmak et al (2022) found a significant difference in their students' algorithm subdimension scores because of their study titled "the effect of the HEM on the cognitive thinking skills of secondary school students."…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no studies on science lesson in the literature, studies indicate that they improve student achievement in social studies courses (Tokmak, 2022). Tokmak et al (2022) found a significant difference in their students' algorithm subdimension scores because of their study titled "the effect of the HEM on the cognitive thinking skills of secondary school students."…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…As a result of the review of the literature, it was seen that the number of studies on the application of HEM is limited. Examining the opinions of 3rd-grade primary school students and their parents regarding HEM (Çimşir et al, 2022); the effect of HEM on the creativity skills of gifted students (Yavuz et al, 2019b); determining students' metaphorical perceptions towards HEM (Ceylan et al, 2020); determining the opinions of teachers who apply HEM about the model (Seçer, 2021); application of HEM in social studies course (Tokmak, 2022); analysis of HEM, which is in the pilot implementation process in Türkiye, in line with the opinions of field experts (Koçoğlu, 2018); studies have been found in the literature, such as the effect of HEM on the cognitive thinking skills of secondary school students (Tokmak et al, 2022); the effect of HEM on the development of problem solving skills of secondary school students (Tokmak, 2023).…”
Section: Introductionmentioning
confidence: 99%